2003
DOI: 10.1161/01.cir.0000096054.18485.07
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Pregnancy-Associated Plasma Protein A Predicts Outcome in Patients With Acute Coronary Syndrome but No Troponin I Elevation

Abstract: Background-Risk stratification in troponin (cTn)-negative acute coronary syndrome (ACS) remains a clinical challenge.We investigated the predictive value of circulating pregnancy-associated plasma protein A (PAPP-A), a novel marker of atherosclerotic plaque activity, in these patients. Methods and Results-Two hundred consecutive hospitalized ACS patients were included, of whom 136 (69 men and 67 women; meanϮSD age, 66Ϯ16 years) remained cTnI-negative for up to 24 hours. PAPP-A was measured at admission, 6 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
2
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(155 citation statements)
references
References 17 publications
10
135
2
8
Order By: Relevance
“…Pregnancy associated plasma protein-A appeared to be an independent predictor of future ischaemic events as well as the need for percutaneous coronary intervention (PCI) or coronary artery bypass graft surgery. 5 Similar findings were reported by Heeschen et al 6 who observed raised PAPP-A in ACS than stable angina and patients without evidence for CAD. Mean PAPP-A levels in NSTEMI patients did not significantly differ from mean PAPP-A levels in UA.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Pregnancy associated plasma protein-A appeared to be an independent predictor of future ischaemic events as well as the need for percutaneous coronary intervention (PCI) or coronary artery bypass graft surgery. 5 Similar findings were reported by Heeschen et al 6 who observed raised PAPP-A in ACS than stable angina and patients without evidence for CAD. Mean PAPP-A levels in NSTEMI patients did not significantly differ from mean PAPP-A levels in UA.…”
Section: Discussionsupporting
confidence: 82%
“…Later, several studies have reported that circulating (elevated) levels of PAPP-A, independently predict the risk of an ischaemic event. 5,6 Uncomplexed form of PAPP-A is elevated in ACS. Binding of pro major basic protein (MBP) to PAPP-A molecule is hindered due to oxidative stress in the microenvironment of the plaque.…”
Section: Introductionmentioning
confidence: 99%
“…53 PAPP-A levels Ͼ10 mIU/L were found to identify ACS with a sensitivity of 89% and a specificity of 81%, but the study population was small. 54 A larger population was studied by Lund and colleagues, 55 who found a strong correlation between PAPP-A and the combined end point death-MI-revascularization at 6 months in 200 patients with ACS. In this study, CRP was also an independent marker of risk but no comparison between the 2 was made.…”
Section: Other Inflammatory Markersmentioning
confidence: 99%
“…9 PaPPA levels following chest pain predict the risk of MI and revascularization. 10 PaPPA is a proatherosclerotic metalloproteinase 11 that has been isolated in other damaged tissue. It has been found to promote repair, thus revealing its role as an inflammation suppressor.…”
Section: Article P 2197mentioning
confidence: 99%